Some Alternative Definitions of Size - Gupta, Nina (Academy of Management Journal, 1980)
The article discusses a number of definitions of organizational size. According to the author, there are three perspectives related to the definition of organizational size. They include the cycles, the energic and the components approaches. The author notes that the cycles approach discusses size as a structural characteristic of an organization. The energic approach concerns itself with both human and material resources used by organizations. According to the author, the components approach takes its definition of size from common usage and tradition.